KAP study on cervical cancer and human papillomavirus vaccine acceptability among adolescent girls of Eastern UP: a cross sectional study - Kumari, Seema; Singh, Aradhana; Sangal, Renu; Sharma, Neela R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Human papillomavirus (HPV) is the most common sexually transmitted infection and is a causal factor for cervical cancer in virtually 100% cases. Despite the availability of highly effective vaccine against HPV, the burden of this dreaded disease remains high in our country. The aim of this study was to study the knowledge, attitude and practices on cervical cancer and HPV vaccine among adolescent girls of Eastern UP and to study the factors influencing knowledge, attitude and practices towards HPV vaccination among adolescent girls of this region. Methods: This was a questionnaire based cross-sectional study. Purposive sampling was used. Sample consisted of adolescent girls attending Gynecological OPD of a tertiary care center of Eastern UP, for a period of one year and the sample size was 384. Results: The results showed that, only 8.07% participants had heard of HPV infection and 2.08% participants had HPV vaccine knowledge. 35.95% participants agreed that their parents would pay for vaccine and 79.17% participants agreed for vaccination, if it would be free of cost. In total, most of the participants in the sample were found to have a positive attitude towards the vaccine. Conclusions: Although the knowledge and awareness of cervical cancer and its prevention through HPV vaccination, was poor among adolescent girls of Eastern UP region, it was encouraging to find, that most of them had a positive attitude towards HPV vaccination. It was also concluded, that the acceptability would increase, if the Government includes HPV vaccination in the National Immunization Program. If the cost constraint is dealt with, this completely preventable disease could be controlled in our country.